Sosialisasi Aspek Hukum dan Ekonomi terhadap Kejahatan Geng Motor pada Kalangan Remaja di Dusun X Desa Medan Krio - Munthe, Riswan; Maswandi, Maswandi; Utama Nst, Amrin Mulia (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Socialization of motorcycle gang crimes among teenagers that are increasingly rampant in the community where the perpetrators are minors who are members of motorcycle gang community groups. What is more interesting about the phenomenon of motorcycle gang groups is that the actions they take are brutal and disrupt public order, there are many violations that have an impact on the community. Therefore, it is necessary to convey to the community the legal aspects of motorcycle gang crimes and sanctions for motorcycle gang perpetrators, because motorcycle gangs are groups of young people (teenagers) who mostly have the same background, are still in school and are underage, who are members of a community of two-wheeled motor vehicle users. The method used in Community Service activities is a method of providing counseling, namely delivering material, which is then carried out in-depth discussions with participants from the mosque congregation and residents of Hamlet X, Medan Krio Village. The discussion began with the presentation of material on Motorcycle Gang Crimes among teenagers. Furthermore, residents of Hamlet X, Medan Krio Village asked questions, then continued an intense discussion with the speaker regarding the problem of motorcycle gang crimes.